Rethinking Discrimination in Christian Fellowship: Theological Implications of James 2:1–13 for Gen Z - Claudia Angelina; Joko Priyono (DIEGESIS: Jurnal Teologi Kharismatika, 2026)
This article examines the theological implications of discrimination in Christian fellowship through an exegetical reading of James 2:1–13 in relation to the Gen Z community. Using a qualitative approach grounded in historical-critical exegesis and theological literature analysis, this study argues that James’s prohibition of partiality is not merely a moral warning against social inequality, but a theological critique of communal practices that contradict faith in Jesus Christ, the royal law of love, and the community’s accountability before divine judgment. The analysis shows that the rich-poor contrast in James 2:1–13 functions as a concrete case through which the text exposes a broader ecclesial disorder, namely the tendency to assign differential worth according to outward status and visibility. In dialogue with practical-theological studies on Gen Z, the article further argues that the passage remains highly relevant in a context where younger generations evaluate Christian communities through justice, authenticity, participation, and belonging. This study contributes an integrative theological framework that connects biblical exegesis, discrimination in Christian fellowship, and the practical-theological horizon of Gen Z, while proposing James 2:1–13 as a normative resource for evaluating ecclesial belonging in contemporary church life. Abstrak Artikel ini mengkaji implikasi teologis diskriminasi dalam persekutuan Kristen melalui pembacaan eksegetis Yakobus 2:1–13 dalam kaitannya dengan komunitas Generasi Z. Dengan menggunakan pendekatan kualitatif yang berlandaskan eksegesis historis-kritis dan analisis literatur teologis, kajian ini berargumen bahwa larangan Yakobus terhadap keberpihakan bukan sekadar peringatan moral terhadap ketimpangan sosial, melainkan kritik teologis terhadap praktik komunal yang bertentangan dengan iman kepada Yesus Kristus, hukum kerajaan tentang kasih, dan pertanggungjawaban komunitas di hadapan penghakiman ilahi. Analisis ini menunjukkan bahwa kontras kaya-miskin dalam Yakobus 2:1–13 berfungsi sebagai kasus konkret yang melaluinya teks tersebut menyingkapkan kekacauan eklesial yang lebih luas, yakni kecenderungan untuk menetapkan nilai yang berbeda berdasarkan status dan penampilan lahiriah. Dalam dialog dengan kajian teologi praktis tentang Generasi Z, artikel ini selanjutnya berargumen bahwa perikop tersebut tetap sangat relevan dalam konteks ketika generasi muda menilai komunitas Kristen melalui keadilan, autentisitas, partisipasi, dan rasa keberterimaan. Kajian ini menyumbangkan kerangka teologis integratif yang menghubungkan eksegesis biblika, diskriminasi dalam persekutuan Kristen, dan horizon teologis-praktis Generasi Z, sekaligus mengusulkan Yakobus 2:1–13 sebagai sumber normatif untuk mengevaluasi keberterimaan eklesial dalam kehidupan gereja masa kini.